2021
DOI: 10.1109/jbhi.2021.3060035
|View full text |Cite
|
Sign up to set email alerts
|

Eliminating Indefiniteness of Clinical Spectrum for Better Screening COVID-19

Abstract: The coronavirus disease 2019 (COVID-19) has swept all over the world in the last few months. Due to the limited detection facilities and medical resources, especially in developing countries, a large number of suspected cases can only receive common clinical diagnosis rather than more effective detections like Reverse Transcription Polymerase Chain Reaction (RT-PCR) tests or CT scans. This motivates us to develop a quick screening method on suspected patients via common clinical diagnosis results. However, the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(15 citation statements)
references
References 54 publications
0
15
0
Order By: Relevance
“…Some researchers have compared and analyzed artificial neural network with random forest and other classification models. For example, in terms of epidemic research, Wang et al [ 29 ], Guo et al [ 30 ], and Oliveira et al [ 31 ] compared the efficiency of neural network, random forest and support vector machine models in the auxiliary diagnosis of AIDS and COVID-19, and results showed that the accuracy of the neural network model is higher than that of other models. In studies on other diseases, Yu et al [ 32 ], Choi et al [ 33 ], Lai et al [ 34 ], Shh et al [ 35 ] all made a comprehensive comparison among neural network, random forest and support vector machine in their respective studies, and concluded that the neural network model was more accurate than random forest and support vector machine models.…”
Section: Discussionmentioning
confidence: 99%
“…Some researchers have compared and analyzed artificial neural network with random forest and other classification models. For example, in terms of epidemic research, Wang et al [ 29 ], Guo et al [ 30 ], and Oliveira et al [ 31 ] compared the efficiency of neural network, random forest and support vector machine models in the auxiliary diagnosis of AIDS and COVID-19, and results showed that the accuracy of the neural network model is higher than that of other models. In studies on other diseases, Yu et al [ 32 ], Choi et al [ 33 ], Lai et al [ 34 ], Shh et al [ 35 ] all made a comprehensive comparison among neural network, random forest and support vector machine in their respective studies, and concluded that the neural network model was more accurate than random forest and support vector machine models.…”
Section: Discussionmentioning
confidence: 99%
“…An attempt is made to develop a rapid screening method with common clinical diagnosis results on suspicious patients. However, the differences in the diagnostic research characteristics of the patients make it difficult for these efforts to yield results (27).…”
Section: Discussionmentioning
confidence: 99%
“…Extensive experiments have demonstrated that GANs can effectively deal with the problem of too few samples in datasets. For example, author ( Gomathi et al, 2020 ) used GAN to generate synthetic medical images to improve the accuracy of classification performance; author ( Guo et al, 2021 ) proposed a GAN-based architecture for limited training data scenarios, and the result was a model capable of Diversity is achieved in the generated samples. Author ( Niu et al, 2021 ) also used GAN as a data augmentation method to show that it can improve performance in tumor segmentation.…”
Section: Methodsmentioning
confidence: 99%